Pengaruh Sari Kacang Hijau Terhadap Peningkatan Kadar HB Pada Ibu Hamil Trimester III - Mas’amah, Mas’amah; Utami, Iis Tri (Utan Kayu Publishing, 2022)
Anemia is a condition where the hemoglobin level is less than normal, which occurs due to a lack of iron in the body where the need for iron increases during pregnancy. One of the efforts to prevent anemia in pregnant women except supplementing blood tablets is the consumption of green beans. A preliminary study conducted at Kotabumi II Public Health Center obtained data from 68 pregnant women who came to have their pregnancy checked as many as 36 (52.94%) third-trimester pregnant women experiencing anemia. The purpose of this study was to determine the effect of green bean extracts on the increase of hemoglobin levels in pregnant women in trimester III at Kotabumi II Public Health Center in 2021. The research type used is a quantitative experimental method with a quasi-experimental approach, namely a non-equivalent control group design. The population in this study were third-trimester pregnant women who came to Kotabumi II Public Health Center totaling 36 people. The sample in this study amounted to 20 people. The sampling technique used was purposive sampling. Univariate and Bivariate analysis using independent t-test. The research result of giving green beans extracts in the intervention group before the treatment was 10.3 and after treatment was 10.7. In the control group before the treatment was 10,07 and after treatment was 10,14 and on average showed the effect of green beans extracts on the increase of Hb levels in pregnant women with a p-value of 0.001. It is hoped that pregnant women can consume green bean extracts to increase the mother's Hb levels. Abstrak: Anemia adalah suatu kondisi kadar hemoglobin kurang dari normal yang terjadi karena kurangnya zat besi pada tubuh dimana saat hamil kebutuhan zat besi meningkat. Salah satu upaya dalam mencegah anemia pada ibu hamil selain tablet tambah darah dengan konsumsi kacang hijau. Studi pendahuluan yang dilakukan di Puskesmas Kotabumi II didapatkan data dari 68 ibu hamil yang datang memeriksakan kehamilannya 36 (52,94%) ibu hamil trimester III mengalami anemia. Tujuan penelitian ini adalah untuk mengetahui pengaruh sari kacang hijau terhadap peningkatan kadar Hb pada ibu hamil trimester III di Puskesmas Kotabumi II Tahun 2021. Jenis penelitian yang digunakan adalah kuantitatif metode eksperimental dengan pendekatan quasy eksperimen yaitu non equivalent control group design. Populasi dalam penelitian ini ibu hamil Trimester III yang datang ke Puskesmas Kotabumi II berjumlah 36 orang. Sampel dalam penelitian ini berjumlah 20 orang. Tehnik sampling yang di gunakan yaitu purposive sampling. Analisa Univariat dan Bivariat menggunakan uji t independen. Hasil penelitian pemberian sari kacang hijau pada kelompok intervensi sebelum adalah 10,3 dan sesudah 10,7. Pada kelompok kontrol sebelum adalah 10,07 dan sesudah adalah 10,14 dan rata-rata menunjukkan adanya pengaruh sari kacang hijau terhadap peningkatan kadar HB pada ibu hamil dengan hasil p value 0,001. Diharapkan ibu hamil dapat mengkonsumsi sari kacang hijau untuk meningkatkan kadar Hb ibu.